2014
DOI: 10.1108/intr-11-2013-0233
|View full text |Cite
|
Sign up to set email alerts
|

Tweet or “re-tweet”? An experiment of message strategy and interactivity on Twitter

Abstract: Purpose – Although a large number of prior studies have discussed the impact of using social media to organizations, the existing literature has not yet provided a clear guidance on what specific communication strategy organizations should adopt on social media and what relationship they need to establish with the public. To fill this theoretical gap, the purpose of this paper is to examine the effects of message strategy and interactivity from a relationship-building perspective within a socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 48 publications
0
40
0
1
Order By: Relevance
“…Previous research has identified characteristics of tweets that are associated with higher levels of retweeting: for example, textual content (e.g., Araujo et al, 2015;Auger, 2014);hashtags (e.g., boyd et al, 2010;Suh et al, 2010), and interactivity (e.g., Burton and Soboleva, 2011;Li and Li, 2014). There have been mixed results on the effect of mentions on retweeting: Yang and Counts (2010) found that tweets containing mentions were more likely to be retweeted, but other authors have found that mentions decreased the number of retweets (Soboleva et al, 2015;Suh et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified characteristics of tweets that are associated with higher levels of retweeting: for example, textual content (e.g., Araujo et al, 2015;Auger, 2014);hashtags (e.g., boyd et al, 2010;Suh et al, 2010), and interactivity (e.g., Burton and Soboleva, 2011;Li and Li, 2014). There have been mixed results on the effect of mentions on retweeting: Yang and Counts (2010) found that tweets containing mentions were more likely to be retweeted, but other authors have found that mentions decreased the number of retweets (Soboleva et al, 2015;Suh et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…While it is entirely possible that the IT group retweeted content could be viewed as evidence that they played a supporting role in the debate (see also work on message strategies by Li and Li, 2014). However, another interpretation focuses on expertise rather than leadership in this debate.…”
Section: Discussionmentioning
confidence: 99%
“…Such frequencies can help establish which groups appeared to share information more widely. The focus was on which Twitter users responded to, rather than initiated, a tweet (see also research on credibility and favourability of communal versus exchange tweets by Li and Li, 2014). The analysis was conducted with all identifiable user groups, excluding the unclassified group (IT professional, legal, finance, entrepreneur, press, and marketing, n = 44,673).…”
Section: Rq3 -Rt Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversos estudios han encontrado que la interactividad en los mensajes influye positivamente en la actitud hacia la compañía, generando credibilidad y compromiso de los seguidores (Li & Li, 2014;Men & Tsai, 2015;Laroche et al, 2013;Kim, Sung, & Kang, 2014). En consecuencia, algunos autores proponen diferentes herramientas que pueden favorecer una gestión más estratégica y dialógica que promueva la participación de los usuarios: preguntas, concursos o sorteos (Men & Tsai, 2012;Sisson, 2017), contenidos de estilo de vida (IAB, 2016), funciones multimedia (Kim, Kim, & Sung, 2011;Gao, 2016), o la inclusión de enlaces (Aced & Lalueza, 2016).…”
Section: Socialesunclassified